Principal's Strategy for Instructional Quality - Juhaini, Juhaini; Harapan, Edi; Kesumawati, Nila (Journal of Social Work and Science Education, 2022)
This study is to outline the Principal's Strategy for Improving Learning Quality at SMPN 1 Banyuasin III Banyuasin Regency. This study employs a qualitative approach. Teachers from SMP Negeri 1 Banyuasin III participated in the study as informants. In this study, data were gathered through interviews, observation, and documentation. The study's findings indicate that the principal's strategy for improving the quality of learning at SMPN 1 Banyuasin III, Banyuasin III Regency is quite good, but there are still several constraints, such as teachers who are not linear with their teaching tasks, low teaching motivation, and limited infrastructure.